Penyusunan Prosedur Operasional Baku Aspek Sistem Manajemen Keselamatan Dan Kesehatan Kerja (Smk3) Di Balai Perawatan Perkeretaapian Ngrombo - Rili, Rianto; Ose A, Julianus Lanang; Ridwan, Ridwan (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2021)
Every activity process in a company cannot be separated from everything, the risk of occupational accidents to workers. So, in a company, an Occupational Safety and Health (K3) program is needed to reduce and prevent work accidents. This study aims to determine the safety aspects that have been implemented and to develop Standard Operational Procedures for the K3 aspects at the Balai Perawatan Perkeretaapian Ngrombo. Data collection methods in this study were observation of maintenance activities, survey of safety facilities, and data on the availability of personal protective equipment. Based on the results of the study, it can be seen that the implementation of K3 at the Balai Perawatan Perkeretaapian is quite good and in accordance with applicable regulations, but there are several safety facilities that are not yet available. Based on the results of the study, suggestions that can be given are that the Balai Perawatan Perkeretaapian should improve the quality of safety facilities and need to apply Standard Operational Procedures for occupational safety and health (K3) aspects so that the safety of all employees is guaranteed.